Pendekatan Emosional dan Spiritualitas dalam Pendidikan Agama Islam sebagai Upaya Pemenuhan Aktualisasi Diri untuk Pembentukan Akhlak Siswa - Medina Nur Asyifah Purnama; Wiwin Rif'atul Fauziyati (CV Edujavare Publishing, 2025)
This study aims to analyze and describe how the emotional and spiritual approach in Islamic Religious Education can be a strategy to fulfill students' self-actualization in the formation of morals in elementary school environments. This study uses a qualitative method with a library research approach that examines various scientific literature related to the emotional and spiritual approach in Islamic education. Data sources consist of primary literature such as Maslow's theory, Al-Ghazali's thoughts, and the Qur'an and Hadith, and secondary sources in the form of journals, books, and other scientific works. Data were collected through documentation studies, categorized into certain sub-themes, and analyzed using content analysis techniques. Data analysis was carried out descriptively-analystically through three stages: data reduction, data presentation, and drawing conclusions. The results of the study show that the emotional and spiritual approach in Islamic Religious Education learning contributes significantly to the formation of students' morals. Teachers play a role not only as conveyors of material, but also as role models who build a learning atmosphere that touches the hearts and inner awareness of students. This approach encourages positive changes in student behavior, such as increased responsibility, honesty, politeness, and social concern. In addition, this approach also helps students in managing emotions, growing spiritual awareness, and creating strong emotional bonds between teachers and students in a warm learning atmosphere.